Pelatihan Pemanfaatan Limbah Botol Plastik Sebagai Media Hidroponik Pada Guru dan Siswa di SMA Hang Tuah Makassar - Nur, Surahman; Yunus, Irham Maulana; Oktarina, Harti; H, Herlina; Aswad, Sitti Hajar (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Waste, especially plastic waste, is a very serious environmental problem faced by society in general. This problem is caused by an imbalance between the ability to manage waste and the production of waste. One way that can be done is to innovate in the utilization of plastic waste, as an effort to reduce its negative impact on the environment. In order to support this effort, this Community Service (PKM) activity was held at SMA Hang Tuah Makassar with a focus on training in the utilization of plastic bottle waste as a hydroponic medium. This training involved teachers and students of SMA Hang Tuah as the main participants, with the aim of introducing environmentally friendly and sustainable farming methods. The methods used were lectures and direct practice. The results of this activity were that students were able to utilize the school yard as a hydroponic plant medium. One of the results of the implementation of community partnerships is as follows: (1) partners learn about hydroponic models that can be used to grow vegetables, (2) partners learn about how to design hydroponic installations using used materials, and (3) partners learn to make a simple hydroponic system using used bottles. The survey results also showed that partners were quite satisfied with this community service activity.